PENGARUH VARIASI DEBIT UDARA TERHADAP KARAKTERISTIK ALIRAN DUA FASE PADA AIRLIFT PUMP DENGAN SUDUT INJECTOR 15° - Auzan Faizdaffa Hakim; Trisma Jaya Saputra; Nurmala Dyah Fajarningrum (Scientific Journal of Mechanical Engineering Kinematika, 2026)
Airlift pump is a type of pumping system that utilizes the density difference between air and water to create two-phase flow, commonly applied in closed-loop circulation systems. This study aims to investigate the effect of varying air flow rates on the characteristics of two-phase flow in an airlift pump with a 15° swirl injector. The experimental method was used with air flow variations of 30, 40, 50, and 60 liters per minute (lpm), focusing on parameters such as superficial velocity of liquid and gas, liquid hold-up, gas volumetric quality, and observed flow patterns. The results show that increasing the air flow rate significantly raises the superficial velocities of both liquid and gas. Furthermore, liquid hold-up tends to decrease with higher air flow rates, while gas volumetric quality increases. The observed flow patterns include bubble, slug, and churn flows, each formed depending on the level of injected air flow. Overall, increasing the air flow rate has a significant impact on the hydrodynamic characteristics of the airlift pump system.